Detection of human noroviruses in sewage by next generation sequencing in Shandong Province, 2019–2021 - Suting Wang; Mingyi Xu; Xiaojuan Lin; Ping Xiong; Yao Liu; Aiqiang Xu; Meng Chen; Shengxiang Ji; Zexin Tao (Virology Journal)
Abstract Background Human noroviruses are the major cause of acute gastroenteritis and exhibit considerable genetic diversity. Next generation sequencing (NGS) analysis based on environmental surveillance has been proved to be an effective method in norovirus surveillance. Methods Between January 2019 and December 2021, 36 sewage samples were collected and analyzed using real-time quantitative PCR to detect noroviruses. Partial VP1 region was amplified and subjected to NGS analysis to assess the abundance and genetic characterization of various norovirus genotypes across different samples. Results A total of 23 norovirus genotypes were identified, including 9 genotypes of GI, 13 genotypes of GII and 1 genotype of GIX. The most frequently detected genotypes were GI.5 (86.11%), GII.2 (86.11%), GII.4 (63.89%), GII.17 (58.33%), and GII.13 (55.56%). Additionally, some rare genotypes, such as GI.7, GII.5, GII.9, and GII.16, which had not been previously reported in Shandong, were identified. No significant differences were observed in genotypic diversity or viral copy numbers in sewage samples when comparing pre- and post-COVID-19 periods. A total of 379 partial VP1 sequences were obtained, with the means sequence identity within a genotype of Shandong sequences ranging from 92.69 to 98.37% and a coefficient of variation ranging from 1.46 to 6.73%. Phylogenetic analysis indicated that local noroviruses within each genotype comprised multiple co-circulating lineages. Conclusions Our data demonstrate that sewage contains noroviruses with considerable high diversities. NGS based environmental surveillance greatly improves the understanding of norovirus circulation and should be encouraged.